Enhancing Critical Gender Consciousness in Social Studies Education: Perspectives from Women Social Activists in Child Protection Programs - Minasyan, Sona; Supriatna, Nana; Sapriya, Sapriya; Malihah, Elly (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to explore how women social activists in Sukabumi, Indonesia, understand and address gender inequality through child protection programs, and to examine how their experiences can inform the development of gender-sensitive Social Studies education. The research seeks to bridge grassroots gender activism with formal educational practice by identifying practical strategies for enhancing critical gender consciousness in Social Studies curriculum. Method: Employing a qualitative approach, the study conducted semi-structured interviews with ten women social activists actively involved in child protection initiatives in Sukabumi. Data were analyzed using thematic analysis to identify patterns and insights regarding gender awareness, community engagement, and educational implications. The conceptual framework integrates perspectives from feminist pedagogy, critical social studies education, and community-based knowledge production. Results: Findings reveal that activists perceive gender inequality as manifested through economic disparities, limited political participation, and entrenched cultural stereotypes. Child protection programs serve as effective platforms for raising gender awareness through community dialogues, advocacy campaigns, and participatory workshops. Key lessons include the importance of contextual understanding, intersectional approaches, and connecting gender issues to broader themes of social justice and citizenship. Novelty: This study contributes original empirical insights from grassroots women activists whose perspectives are often underrepresented in educational research. It offers a practical model for integrating community-based gender knowledge into formal Social Studies education, particularly in the Indonesian context. The research demonstrates how activist experiences can enrich pedagogical approaches and foster critical gender consciousness among students.